Handbook of blockchain, digital finance, and inclusion: Cryptocurrency, FinTech, InsurTech, and regulation - LEE, David (Institutional Knowledge at Singapore Management University, 2018)
The volume explores recent advances in digital banking and cryptocurrency, emphasizing mobile technology and evolving uses of cryptocurrencies as financial assets. Contributors go beyond summaries of standard models to describe new banking business models that will be sustainable and will likely dictate the future of finance. The volume not only emphasizes the financial opportunities made possible by digital banking, such as financial inclusion and impact investing, but it also looks at engineering theories and developments that encourage innovation.